Regularities and Development Trends of Agricultural Cooperation in Central Asia - Yegizbayeva, Gulnur; Rakhimzhanova, Gaukhar; Jumabayeva, Aigul; Assanov, Beibit; Kuralbaeva, Roza (International Journal of Economics and Financial Issues, 2015)
In this article the author attempts to give an idea of the today’s progress in formation of agricultural cooperatives in the five countries of Central Asia. The study has shown that agriculture of the countries under consideration is dominated by small agricultural producers. However, the lack of market infrastructure does not allow them to become active players in the market. The results of the systemic analysis revealed that the development process of agricultural cooperatives is quite chaotic in nature, the level of cooperation is rather low, and the impact of agricultural cooperatives on national agribusiness is so far barely noticeable. Taking into account the feasibility and potential for the development of cooperatives in the countries of Central Asia, the author considers the main directions of encouragement of agricultural associations. Keywords: agricultural cooperation, service cooperative, production cooperative, collective farming, supporting cooperative, consumer cooperation, cooperative legislation. JEL Classifications: Q120, Q130, R21, R22